Peran Sekolah, Pemerintah Lokal, dan Pendidikan Jasmani dalam Pencegahan Stunting Anak di Desa Kubang Utara Sikabu, Sawahlunto - Sandra Dewi; Sesi Ulul Azizah; Adria Fahyumi Alfanzha; Mila Nor Elijha; Alsyahidan Arsyad (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Stunting is a serious health problem that hinders children's physical growth and cognitive development due to long-term malnutrition. This study aims to explain the role of government, community participation, and school contributions in preventing stunting in Kubang Utara Sikabu Village, Sawahlunto. The method used was descriptive qualitative through interviews, observations, and document studies. The results showed that stunting remains a government priority, with a prevalence decline from 21.1% (2021) to 13.6% (2022). The community is beginning to understand stunting, but the implementation of healthy eating habits is still suboptimal. Parents are quite active in supporting children through Integrated Health Posts (Posyandu), although access to nutritional assistance and school involvement in nutrition education remains limited. This study emphasizes the importance of synergy between the government, schools, and the community to improve parental knowledge for better parenting practices, thereby continuing to reduce stunting rates.